Optional Protocol on a Communications Procedure - Benyusz , Márta (International Children’s Rights, 2024)
The Optional Protocol to the Convention on the Rights of the Child on a communications procedure (hereinafter OPIC) was adopted on December 19, 2011, and entered into force on April 14, 2014. It opened the possibility for individual complaints to be brought to the Committee on the Rights of the Child (hereinafter CRC Committee or Committee) whenever domestic remedies were exhausted, in cases of the occurrence of an alleged violation to the provisions of the United Nations (UN) Convention on the Rights of the Child (CRC) or its two Optional Protocols, by state parties to any of these international instruments, as well as when for an unreasonably long time no step was taken by the given state to address the alleged violation. The main aim of the OPIC was to enhance children’s access to their rights, especially to effective remedy at an international level. The OPIC was also the last piece of the puzzle in the UN treaty body system, as its adoption led all UN treaty bodies to have the competence to receive individual communications procedures. Nevertheless, although the CRC itself is the most widely ratified human rights treaty and the other two Optional Protocols have a very wide acceptance, the OPIC has a low rate of signatory states and an even lower ratification rate. Keywords: United Nations Convention on the Rights of the Child, children’s rights, Optional Protocols, OPIC, CRC Committee, State Party, remedy, interim measures, individual communications, Inter-State complaint, inquiry procedure, legal capacity of a child